Dynamic Modeling and Simulation of Short-Duration Over-excitation Phenomenon in Hysteresis Motor - Sayyed Hossein Edjtahed; Amir Hossein Pir Zadeh; Abolfazl Halavaei Niasar (Institute of Advanced Engineering and Science, 2017)
The hysteresis motor is a well-known synchronous motor that is used in special small power, high speed applications. Dynamic modeling and analysis of this motor is more complicated than permanent magnet synchronous motors (PMSMs) or induction motors (IMs) due to nonlinear behavior of rotor magnetic material. Short over-excitation is a unique phenomenon that only occurs in hysteresis motor in which the terminal voltage increase at synchronous speed for a short duration, and then continuously is decrease to initial value. Therefore, the input current is reduced, this leads to more power factor and efficiency enhancement. Till now, there isn’t any analytic dynamic model of this phenomenon. In this paper, based on a novel dynamic model of hysteresis motor, the over-excitation phenomenon is investigated and transient performance of the motor during over-excitation is simulated via Simulink.